Landscape of Carbon Ion Radiotherapy in Prostate Cancer: Clinical Application and Translational Research - Chen, Xue; Yu, Qi; Li, Ping; Fu, Shen (Frontiers in Oncology, 2021)
Carbon ion radiotherapy (CIRT) is a useful and advanced technique for prostate cancer. This study sought to investigate the clinical efficacy and translational research for prostate cancer with carbon ion radiotherapy. We integrated the data from published articles, clinical trials websites, and our data. The efficacy of CIRT for prostate cancer was assessed in terms of overall survival, biochemical recurrence-free survival, and toxicity response. Up to now, clinical treatment of carbon ion radiotherapy has been carried in only five countries. We found that carbon ion radiotherapy induced little genitourinary and gastrointestinal toxicity when used for prostate cancer treatment. To some extent, it led to improved outcomes in overall survival, biochemical recurrence-free survival than conventional radiotherapy, especially for high-risk prostate cancer. Carbon ion radiotherapy brought clinical benefits for prostate cancer patients, and quality of life assessment indicated that CIRT affected patients to a lesser extent. Potential biomarkers from our omics-based study could be used to predict the efficacy of prostate cancer with CIRT. Carbon ion radiotherapy brought clinical benefits for prostate cancer patients. The omics-based translational research may provide insights into individualized therapy.